'Settling In': Exploring the complexities of observing and responding to young children's communications of distress as they start day care. Issue 3 (1st September 2020) - Brace, Debbie
ABSTRACT: This paper uses material from two psychoanalytic observations of children in day care to illustrate ways in which young children communicate their feelings on separating from their parents. It discusses how early years practitioners respond to children's distress as they form a Key Person relationship. Points are raised about how difficult it can be for practitioners to respond to children in the early days of them getting used to the new environment, especially in the absence of a robust, reflective work culture. The child's Key Person may avoid understanding children's distress and even misinterpret the child's communication. The paper presents detailed observations of a young girl, who in the absence of an available and receptive adult, finds ways to distance herself from or to cut off from missing her mother and longing to go home. Her defensive, or self protective response, arguably leads to more difficulty for her Key Person, to notice, understand and respond sensitively to her expressions of distress. The paper argues for better, supportive, reflective systems for early years practitioners working in day care, in order to improve the emotional experience for them and for the children.